Hurricanes, industrial animal operations, and acute gastrointestinal illness in North Carolina, USA - Arbor J L Quist; Mike Dolan Fliss; David B Richardson; Paul L Delamater; Lawrence S Engel (Environmental Research: Health)
North Carolina (NC) ranks third among US states in both hog production and hurricanes. NC’s hogs are housed in concentrated animal feeding operations (CAFOs) in the eastern, hurricane-prone part of the state. Hurricanes can inundate hog waste lagoons, transporting fecal bacteria that may cause acute gastrointestinal illness (AGI). While CAFOs and hurricanes have separately been associated with AGI, few epidemiological studies have examined the joint effect of hurricanes and CAFOs. We examined the impacts of Hurricanes Matthew (2016) and Florence (2018) on the occurrence of post-storm AGI in areas with varying numbers of hog and poultry CAFOs. We used ZIP code-level disease surveillance data, 2016–2019, to calculate rates of AGI emergency department (ED) visits in NC. Using precipitation data, CAFO permit data, and interrupted time series methods, we assessed the change in AGI rate during the three weeks after Matthew and Florence in ZIP codes with heavy rain (>75th percentile of storm precipitation) and 0, 1–10, and >10 hog CAFOs. The AGI ED rate in ZIP codes with heavy storm rain and >10 hog CAFOs increased 15% (RR = 1.15, 95% CI: 1.04, 1.27) during the three weeks after Hurricane Florence, although there was little increase after Hurricane Matthew (RR = 1.05, 95% CI = 0.86, 1.24). The AGI ED rates in ZIP codes with heavy storm rain and no hog CAFOs exhibited no increase during these post-hurricane periods (Matthew: RR = 0.97, 95% CI: 0.80, 1.14; Florence: RR = 1.01, 95% CI: 0.89, 1.13). We also observed an increase in AGI ED rate in areas with both >10 hog CAFOs and >10 poultry CAFOs. Areas with heavy hurricane precipitation and many CAFOs had a higher proportion of Black, American Indian, and Hispanic residents and lower annual household incomes than the state averages. Heavy hurricane precipitation in areas with CAFOs may increase AGI rates, disproportionately affecting people of color in NC.